التّخلّق باخلاق الله عند عبد الكريم القشيري - Istifaiyah, Istifaiyah (Teosofia: Indonesian Journal of Islamic Mysticism, 2015)
To behave as God’s attitude and moral (akhlak) is part of the purpose of the creation of man as a Caliph of God on this earth. Humans who are part of the image of Majesty/tajalli of Allah have the potential ilahiyah that is capable of being a medium for glorifying the Earth. Therefore, humans have an obligation themselves to always try to be the ideal image on the side of God. Through the study of analytic description of the at-Tahbir fi at-Tazkir al-Qusyairy works, the author tried to explain al-Qusyairy's view of man as the ideal image of (al-Insan al-Kamil) through the efforts of continually behave as Allah’s behaiour. Al-Qusyairy States that one of the methods to make the humanbeing as a perfect creation is by always working to the imitation of meaning contained in the asthma ' and the nature of God, the sacred, the Asma'ul Husna. However, not all the names and the nature of God can be applied in the attitude and behaviour of human beings. Because, there is a portion of the name and nature of God, who contains oneness, greatness, glory of the substance of God, as the word of God, al-Ahad al-Mutakkabir, etc. While the name and the nature of God that shows the true nature of his actions can be imitated by man, such as al-' Alim al-Latif al-Wahhab al-Khaliq, etc.